2017
DOI: 10.1177/0706743717741058
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Attempts and Completions among Mothers Whose Children Were Taken into Care by Child Protection Services: A Cohort Study Using Linkable Administrative Data

Abstract: Mothers who had a child taken into care had significantly higher rates of suicide attempts and completions. When children are taken into care, physician and social workers should inquire about maternal suicidal behaviour and provide appropriate mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…In addition to the increased risk of suicide among mothers—findings consistent with previous research—we found that mothers are at higher risk for other causes of avoidable mortality, including death due to ischaemic heart disease 8. To our knowledge, this is the first study to examine mortality among fathers whose children were placed in care; we found that fathers whose children are placed in care are also at increased risk of death due to avoidable causes.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to the increased risk of suicide among mothers—findings consistent with previous research—we found that mothers are at higher risk for other causes of avoidable mortality, including death due to ischaemic heart disease 8. To our knowledge, this is the first study to examine mortality among fathers whose children were placed in care; we found that fathers whose children are placed in care are also at increased risk of death due to avoidable causes.…”
Section: Discussionsupporting
confidence: 88%
“…A study of general hospital in‐patients in China showed that suicide risk was highest in people who were aged over 60 and in their cohort suggested that assertive efforts should be made to identify this group early in order to screen to screen for suicidal ideas (Wan, Ding, Hu, et al, ) especially as there is research that shows that physicians are less likely to screen for and record suicide risk in older adults (Raue, ).…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…As this was a qualitative study, the longer-term consequences for the parents cannot be measured. A study by Wall-Wieler et al (2018) indicates an increased risk of suicide attempts and completion among mothers after a child custody loss [46]. The families in this study were severely traumatized, although they were reunited.…”
Section: Discussionmentioning
confidence: 56%